2007
DOI: 10.1177/0886260506298827
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Victims and Perpetrators in a Depicted Child Sexual Abuse Case

Abstract: This study investigated the roles of respondent, perpetrator, and victim gender on attributions toward a 10- or 15-year-old victim and an adult perpetrator in a hypothetical sexual abuse case. It was predicted (a) that female respondents would be more provictim and antiperpetrator than men, (b) that 10-year-old victims would be deemed more credible than 15-year-olds, and (c) that men would deem a 15-year-old male victim more culpable when child sexual abuse is perpetrated by a female abuser. Three hundred thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 21 publications
14
89
3
3
Order By: Relevance
“…Consistent with previous research (e.g., Davies & Rogers, 2004;Rogers & Davies, 2007), independent samples t-tests revealed no significant differences across CSA victims versus nonvictims in any of the dependent measures examined. As such, all respondents' are treated as a homogenous group regardless of their own victim status.…”
Section: Preliminary Analysessupporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with previous research (e.g., Davies & Rogers, 2004;Rogers & Davies, 2007), independent samples t-tests revealed no significant differences across CSA victims versus nonvictims in any of the dependent measures examined. As such, all respondents' are treated as a homogenous group regardless of their own victim status.…”
Section: Preliminary Analysessupporting
confidence: 84%
“…Men tend to make more negative attributions toward child victims than women (Back & Lips, 1998;Broussard & Wagner, 1988;Davies & Rogers, 2004;Eisenberg et al, 1987;Maynard & Weiderman, 1997;Reynolds & Birkimer, 2002;Rogers & Davies, 2007). In Broussard and Wagner's (1988) study, men considered male victims particularly responsible when the victim's behavior was encouraging.…”
Section: Respondent Gendermentioning
confidence: 88%
See 1 more Smart Citation
“…Studies of child sexual abuse have demonstrated that the gender of the abuser strongly determines how offenders are perceived, with men viewed more negatively than women (Bornstein et al 2006;Rogers and Davies 2007). The four key studies on perceptions of adult-teen sexual relationships examined how the genders of the adult and teen influenced perceptions.…”
Section: Perceptions Of Adult-teen Sexual Relationshipsmentioning
confidence: 97%
“…Other research has revealed differences in evaluation of sexual abuse victims depending on perpetrator and victim gender as well as victim age (Quas, Bottoms, Haegerich, & Nysse-Carris, 2002;Rogers & Davies, 2007). For example, older children who have been sexually abused are judged less positively and as more responsible for what happened to them than younger children.…”
Section: Discussionmentioning
confidence: 95%